ANALISIS PARUH HIDUP LITERATUR PADA REFERENSI BUKU BIDANG ILMU PERPUSTAKAAN - Sri Suharmini Wahyuningsih; Parwitaningsih; Pratiwi Anindita Aji; Henrikus Bambang Prasetyo (Universitas Islam Negeri Salatiga, 2025)
The half-life of literature in bibliometrics is defined as the recency or obsolescence of literature in a field of science. References, or bibliographic data, are a list of sources of information that the author refers to support or complement the writing with statements from other experts in fields related to the subject of the writing. Books are a source of information needed by writers, researchers, and the public who need information related to the field of library and information science. The writing of this article is based on research that aims to measure or evaluate the recency or obsolescence of literature used in writing books in the fields of library and information science. The method used is descriptive with a bibliometric approach, specifically the age and up-to-date references used by book authors. By listing all the years of publication of the references used. The population is books in the field of library and information science published in 2014–2019, with the number of references registered being 1,471. The results that the age of library and information literature was 17 years.